Writing Philippine Cinema, reading Nic Tiongson - Sangil, Anne Frances N. (2017)
Access online through this link: https://www.plarideljournal.org/article/writing-philippine-cinema-reading-nic-tiongson
Keywords: Tiongson, Nicanor G; Motion pictures; Film criticism